2021
DOI: 10.1080/13854046.2020.1871515
|View full text |Cite
|
Sign up to set email alerts
|

Teleneuropsychology clinic development and patient satisfaction

Abstract: Objective: Telehealth offers the opportunity to address a growing need to improve access to specialty services, such as neuropsychology, particularly for older adults and those in rural areas. Initial research has examined the validity and acceptability of teleneuropsychology (teleNP) in research settings, but there is less information about teleNP implementation in clinical practice. Here we describe the development of a teleNP clinic and compare patient satisfaction to those completing in-person neuropsychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 30 publications
4
14
1
Order By: Relevance
“…However there is also evidence that older adults prefer to use online technology for some aspects of their everyday functioning, such as money management ( Sunderaraman et al, 2020 ). Emerging research on the acceptability of TeleNP in various contexts during the COVID-19 pandemic suggests that many examinees find TeleNP services satisfactory ( Appleman et al, 2021 ; Gardner et al, 2021 ; Parsons et al, 2021 ). Prior telepsychiatry research also suggests that patients, especially those with limited access to in-person healthcare services in their communities, are highly satisfied with telehealth services, and in some cases prefer telehealth appointments over in-person visits ( Chong & Moreno, 2012 ; Hilty et al, 2007 ; Shore, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…However there is also evidence that older adults prefer to use online technology for some aspects of their everyday functioning, such as money management ( Sunderaraman et al, 2020 ). Emerging research on the acceptability of TeleNP in various contexts during the COVID-19 pandemic suggests that many examinees find TeleNP services satisfactory ( Appleman et al, 2021 ; Gardner et al, 2021 ; Parsons et al, 2021 ). Prior telepsychiatry research also suggests that patients, especially those with limited access to in-person healthcare services in their communities, are highly satisfied with telehealth services, and in some cases prefer telehealth appointments over in-person visits ( Chong & Moreno, 2012 ; Hilty et al, 2007 ; Shore, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Though there was some apprehension about the usability of video telehealth with older adults due to concerns about technological literacy, research has shown that older adults are interested in learning about new technology and are willing and able to adopt new technology, 21 , 22 with no difference in satisfaction ratings between telehealth and in-person settings. 23 , 24 Multiple recent studies suggest high satisfaction with care and no detriment to the patient-provider relationship among older adults using telehealth.…”
Section: Objectivementioning
confidence: 99%
“…(2014) survey results indicated in their group of healthy older adult participants 17% preferred teleNP and 39% had no preference to testing condition. An in-clinic teleNP method for assessment of regional veterans found participant satisfaction of a full teleNP neuropsychological assessment was high for those assessed in a remote clinic ( Appleman et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In-clinic teleNP utilizes videoconferencing to assess an individual situated in a remote clinic, usually with an assistant on site to aid the assessment ( Appleman et al., 2021 ; Postal et al., 2021 ). This method has typically been used for those living in rural or regional communities or those whom have to travel long distances to attend an assessment.…”
mentioning
confidence: 99%
See 1 more Smart Citation